Changes in the Chemical Composition of Turkish White Cheese According to Storage TemperatureChanges in the Chemical Composition of Turkish White Cheese According to Storage Temperature - Altuner, Ergin Murat; Eljagmani, Salem (University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca, 2020)
The aim of this study is to highlight changes in the chemical composition, namely pH, total dry matter percentage (DM%), total nitrogen and protein, titratable acidity, salt content and biogenic amines, of Turkish white cheese according to storage temperature. The results confirmed that a decrease was observed in pH values of the samples during storage. Titratable acidity was observed to show a trend of increase (P > 0.05). As per these results, there was an increase in DM% in cheese samples stored at all three temperatures, namely 5, 15, and 25°C, on day 11, but a decrease was observed on day 31. An increased trend was seen in samples after day 31. In addition, an increased trend in the amount of salt in the samples, depending on time, was determined. The concentration of biogenic amines, tryptamine, 2-phenylethylamine, putrescine, cadaverine, tyramine, spermidine and spermine, with dominated biogenic amines relate to shelf life, were putrescine, cadaverine, and tyramine, and were increased based on storage temperatures.
Keywords: proximate composition; biogenic amines; turkish white cheese; TP368-456; Food processing and manufacture; 2. Zero hunger